An Extended Emission Line Region around Mrk 1172. Issue Volume 15:Issue S359(2020) (March 2019) - Lassen, Augusto; Riffel, Rogério; Chies-Santos, Ana L.; Johnston, Evelyn; Haeussler, Boris; Dutra, Daniel R.; Azevedo, Gabriel M.
Abstract: We serendipitously found an intriguing Extended Emission Line Region (EELR) near the quiescent and massive early-type Mrk 1172, with a projected extension of approximately 14 × 14 kpc. Its irregular shape, high gas content, strong emission lines and proximity to an isolated possible faded quasar raise questions about the ionization of this gas and the nature of this object. Analyzing the stellar population in both objects we observe that the EELR has a dominance of young-intermediate and intermediate stellar populations (200 Myr < t < 1 Gyr) with significant star formation activity, while Mrk 1172 is dominated by old stellar population ( t > 5 Gyr). BPT diagnostic diagrams indicate that the gas in the EELR is photoionized by hot massive stars rather than by a hard radiation field or by shocks. Further analysis on abundances of the gas and its kinematics shall be performed to better comprehend the nature of this object and how it is interacting with Mrk 1172.